Enhancing Teacher Competence in English Language Teaching Using the Deep Learning Approach - Devi Nurhastuti; Ape Segenil; Iin Inayah Ma’sum (Journal of Innovative and Creativity, 2025)
Teacher competence is crucial for effective learning, particularly in English language teaching. In response to 21st-century educational demands, the deep learning approach has emerged as a strategy to improve teaching quality by emphasizing conceptual understanding, critical thinking, reflection, and real-world application. Within the educational sphere, deep learning fosters meaningful, mindful, and joyful learning experiences—elements that are vital for both student engagement and teacher development. This study employs a literature review to examine the relationship between deep learning and teacher competence improvement in English instruction. Analysis of scholarly sources shows that effective implementation requires teachers to be creative in lesson planning, enhance pedagogical skills, and strengthen professionalism. Additionally, this approach supports reflective teaching and higher-order thinking skills essential for language instruction. Overall, deep learning not only enhances student outcomes but also significantly contributes to developing comprehensive teacher competence.